2013
DOI: 10.1586/14789450.2014.859527
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers of physical activity: candidates and clinical utility

Abstract: Chronic physical inactivity is a major risk factor for a number of important lifestyle diseases, while inappropriate exposure to high physical demands is a risk factor for musculoskeletal injury and fatigue. Proteomic and metabolomic investigations of the physical activity continuum - extreme sedentariness to extremes in physical performance - offer increasing insight into the biological impacts of physical activity. Moreover, biomarkers, revealed in such studies, may have utility in the monitoring of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 154 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…Thus, the establishment of less-invasive and technically uncomplicated biomarker(s) to monitor the disease-stage and the outcome of therapeutic treatment(s) is urgently needed. There is also an unmet need to establish biomarkers to investigate exercise-related muscle damage and repair processes30313940. To resolve these situations, in this study, we developed an ELISA to measure titin N-terminal fragment in human urine, and we demonstrated that the established ELISA is highly sensitive and available for the detection of a wide range of concentrations of titin N-terminal fragment in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the establishment of less-invasive and technically uncomplicated biomarker(s) to monitor the disease-stage and the outcome of therapeutic treatment(s) is urgently needed. There is also an unmet need to establish biomarkers to investigate exercise-related muscle damage and repair processes30313940. To resolve these situations, in this study, we developed an ELISA to measure titin N-terminal fragment in human urine, and we demonstrated that the established ELISA is highly sensitive and available for the detection of a wide range of concentrations of titin N-terminal fragment in urine.…”
Section: Discussionmentioning
confidence: 99%
“…; Claus and Swann ; Sampson et al. ). The low sample volumes required and the amount of information obtained make these approaches attractive for efficiently advancing understanding of the role of nutrition in modulating metabolic responses to military training, identifying novel relationships between nutrition, metabolism, and performance decrements in these environments, and monitoring the temporal dynamics of these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This approach can provide more comprehensive and sensitive markers of metabolic status than commonly measured biomarkers while offering insights into the regulation of metabolic pathways (Sampson et al. ). Metabolomics may therefore provide an efficient method of assessing dynamic metabolic responses to stress and nutritional interventions during military training, and for identifying novel mechanisms modulating performance in these environments (Bradburne et al.…”
Section: Introductionmentioning
confidence: 99%
“…Especially urine proteomics has great potential for discovering new disease indicators that are suitable for the establishment of simple and non-invasive assays [232]. The comparative profiling of the urine proteome has already identified several urinary biomarkers of physical activity [233] and muscle wasting during cancer cachexia [234].…”
Section: Circulating Biomarkers For Monitoring General Muscle Damagementioning
confidence: 99%